University social linkage: A path towards social relevance - Seañez Martínez, Zaide Patricia; Guadarrama Atrizco, Víctor Hugo (Emerging Trends in Education, 2022)
Historically, universities have been a key element of socio-economic, political and technological development of nations. This fact has required a clear and effective relationship with society, which has commonly been called as linkage. Given the importance of this link, the purpose of this article is to review the evolution of the term in order to know what the analysis has focused on, so it allows us to identify the degree of social dimension importance in this relationship. To achieve this task, a historical-theoretical review is carried out of the conception of the university linkage with its environment. This review shows that there is little consensus on how to call it and define it, since there is a risk of falling into generalizations or reductionisms. The study of university-company linkage has been privileged, so this paper proposes the concept of university social linkage as an approach to examine how universities interact with other social actors and towards all areas of reality. It is relevant to highlight that university linkage is a strategy for social relevance, which it is not explored in depth in this document, but is outlined as a future line of research. Keywords: University; Linkage; Social relevance